Об’єкт правовідносин у сфері венчурного інвестування інноваційної діяльності - Жорнокуй, Ю. М.; Подрез-Ряполова, І. В. (НДІ ПЗІР НАПрН України, 2022)
Наукова робота присвячена дослідженню проблем, що виникають щодо визначення об’єкта правових зв’язків у сфері венчурного інвестування інноваційної діяльності. Проаналізовано два основні підходи до розуміння такого об’єкта – об’єкт права промислової власності та інноваційний продукт або технологію. Доведено відсутність аргументів на користь доцільності визнання об’єктом венчурного інвестування інноваційної діяльності інноваційного продукту, оскільки про нього можна говорити у контексті характеристики якісних складових виробленої продукції з урахуванням провадження в інноваційний процес нового об’єкта права промислової власності, отриманого в результаті проведення та отримання нових науково-технічних розробок, результат яких отримав об’єктивну форму (патент, свідоцтво тощо). Технологія також не може визнаватися об’єктом досліджуваних відносин, оскільки її тлумачення у законодавстві та доктрині є досить розмитим, чітко не дає відповіді на запитання про розуміння такого об’єкта, оскільки є переважно узагальнюючим поняттям, яке охоплює весь спектр відносин, що мають місце у ланцюгу інноваційного процесу. Зроблено висновок, що заінтересованість суб’єктів інноваційної діяльності становлять позитивні результати від проведення науково-технічних та конструкторських розробок, результатом яких є створення об’єкту інтелектуальної творчої діяльності, втіленого у певну об’єктивну форму (патент, свідоцтво тощо). Відповідно об’єктом венчурного інвестування інноваційної діяльності є майнові права на втілений у матеріальний носій інтелектуальний продукт, який створено в результаті фундаментальних і прикладних наукових досліджень, результати якого мають практичну придатність, здебільшого промислову, і можуть бути використані для потреб суспільства. Problem setting. The basis of carrying out venture investment into innovation activity is a creative search for opportunities to establish the objective truth of certain processes and, if possible, their implementation into industrial production. Therefore, one can determine by using legislative norms on intellectual property the persons who own the result of intellectual creative activity, embodied into a certain objective form (a patent, a certificate, etc.). However, it is often emphasized, except the objects of industrial property rights, that the objects of venture investment into innovation activity are innovative products or technologies. Analysis of recent researches and publications. The modern research situation of the selected issues indicates the imperfection of the current legislation and the lack of legal doctrine in the context of determining the objects of legal relations of venture investment into innovation activity. Doctrinal developments of domestic and foreign experts, such as Yu. Ye. Atamanov, K. M. Vrublevska-Misiuna, V. P. Kokhan, O. E. Simson, F. Pinkow, J. Iversen, although contain analysis and arguments in favor of a certain scientific approach in the context of understanding the outlined issue, but do not give an unambiguous answer. Significant scientific achievements in considering the development of startups by business incubators and venture financing of startups is the work of O.V. Rozghon. Target of research. The objective of the article is to clarify the issue of determining the object of venture investment into innovation activity. Article’s main body. The author of the research argues against the recognition of innovative products and technologies as the object of venture investment into innovation activity, because: 1) innovative product is only the result of production activities (secondary, derivative object), when there is already the object (the object of intellectual property law) having the security document; such a product can be discussed in the context of the characteristics of quality components of the products, taking into account the implementation of a new object of industrial property rights into the innovation process; 2) the concept of technology as an object contained in the legislation of Ukraine and legal doctrine is rather vague and does not clearly answer the question on understanding the object of researched legal relations, since it is mostly a generalizing concept that covers the entire range of relations taking place in the chain of the innovation process. Conclusions and prospects for the development. The purpose of the activity of the objects of venture investment into innovation activity is to create an object of intellectual, creative activity, i.e. the creation of venture entrepreneurship object, which includes inventions, utility models and other innovations, the creation of which are carried out with a certain risk. The interest of the subjects of innovation activity is the positive results of scientific and technical, engineering developments, the result of which is the creation of an object of intellectual creative activity embodied in a certain objective form (a patent, a certificate, etc.). Accordingly, the object of venture investment into innovation activity is property rights to the intellectual product embodied into the material carrier, which is created as a result of basic and applied scientific research, the results of which have practical applicability, mostly industrial one.
Keywords: венчурне інвестування інноваційної діяльності; промислова власність; інноваційний продукт; venture investment into innovation activity; industrial property; innovative product